Flaky calcium carbonate composite material as well as preparation method and application thereof

Through two -step legal calcium carbonate composite material, nanocrone -like all -silicon molecular sieves are used as grinding medium, which solves the problem of being easily damaged in existing technologies, improved the mechanical properties and gas adsorption of materials, and realized the realization. Improvement of product quality and application.

CN119331434AActive Publication Date: 2025-01-21FUHAI (DONGYING) ADVANCED MATERIAL TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411875969.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-01-21
Estimated Expiration
2044-12-19

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a flaky calcium carbonate composite material as well as a preparation method and application thereof, and relates to the technical field of calcium carbonate. The stripping of calcium carbonate is realized through a two-step method, firstly, in a pre-grinding stage, fibrous light calcium carbonate with a high length-diameter ratio is subjected to preliminary stripping, so that calcium carbonate powder with a relatively high lamellar degree is obtained; then, in the secondary grinding stage, a nano flaky all-silicon molecular sieve is introduced, and the molecular sieve plays a role of grinding a carrier in the secondary grinding process because the structural rigidity of the molecular sieve is obviously higher than that of a calcium carbonate lamella, so that the damage of secondary grinding to the flaky structure of the calcium carbonate is effectively prevented, and the integrity of the flaky structure of the calcium carbonate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of calcium carbonate, and in particular to a flaky calcium carbonate composite material and a preparation method and application thereof. Background Art

[0002] Calcium carbonate is a commonly used high-quality inorganic material and one of the important application products of inorganic chemical industry today. It is widely used in rubber, plastic, paper, coating and other industries. However, due to its small specific surface area and poor surface permeability, the application of general calcium carbonate in rubber and plastic products is limited, especially at high filling amount (≥30wt.%), it has little effect on improving the rigidity and heat resistance of the material. Flaky calcium carbonate has a larger specific surface area and stronger hiding power than conventional calcium carbonate. At the same addition amount, it can achieve a significant improvement in performance and has broad application prospects.

[0003] At present, the production of flaky calcium carbonate adopts mechanical stripping or hydrothermal treatment. Although the method is simple and the production cost is low, the flaky structure is easily destroyed during the grinding process, thus affecting the product quality; and the low yield of hydrothermally treated calcium carbonate also affects its use. Chinese invention patent CN101514028A discloses a method for preparing flaky heavy calcium carbonate powder. The method has the problem that mechanical stripping easily destroys the integrity of flaky calcium carbonate and has low yield.

[0004] Based on the problems existing in the prior art, it is urgent to develop a new method for preparing flaky calcium carbonate to ensure that the flaky structure of calcium carbonate is not destroyed during the grinding process and to ensure product quality. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a flaky calcium carbonate composite material and a preparation method and application thereof, which not only improves the integrity of the calcium carbonate flaky structure, but also can improve the mechanical properties and gas adsorption of modified polypropylene prepared using the flaky calcium carbonate composite material.

[0006] The technical solution of the present invention is: In a first aspect, the present invention provides a method for preparing a flaky calcium carbonate composite material, comprising the following steps: (1) Preparation of nanosheet all-silicon molecular sieve A silicon source, an alkali source, a template agent and deionized water are mixed to form a sol at room temperature, and after aging for 1-4 days, a hydrothermal synthesis is performed at 130-160°C for 10-16 hours. The obtained crystals are repeatedly rinsed with deionized water, centrifuged, dried and calcined to remove the template agent, thereby obtaining a nano-sheet-shaped all-silicon molecular sieve; (2) Preparation of flaky calcium carbonate composite materials S1: adding fibrous light calcium carbonate into water, wherein the fibrous light calcium carbonate accounts for 60-80% of the total mass of the fibrous light calcium carbonate and water; S2 adds a composite grinding aid and disperses to obtain a uniform slurry; the composite grinding aid is sodium polyacrylate, sodium hexametaphosphate and triethanolamine; S3 pre-grinds the slurry at a rotation speed of 70-150 r / min and a grinding time of 30-50 min to pre-strip the fibrous light calcium carbonate to form lamellar calcium carbonate; S4: adding a silane coupling agent and the nano-sheet-shaped all-silicon molecular sieve prepared in step (1) to the pre-ground slurry, and performing secondary grinding at a rotation speed of 60-80 r / min and a grinding time of 60-120 min to obtain a uniform mixed slurry; wherein the mass of the nano-sheet-shaped all-silicon molecular sieve accounts for 5-70% of the total mass of the pre-ground slurry, the silane coupling agent and the nano-sheet-shaped all-silicon molecular sieve; The S5 mixed slurry was repeatedly washed with deionized water and centrifuged to obtain a flaky calcium carbonate composite material.

[0007] Preferably, in step (1), the silicon source is silica sol, tetraethyl orthosilicate or sodium silicate; the alkali source is NaOH; and the template agent is tetrapropylammonium hydroxide, tetrapropylammonium bromide or tetraethylammonium bromide.

[0008] Preferably, in step (1), the molar ratio of the silicon source, the alkali source, the template and the deionized water is 1:(2-4):(0.02-0.06):(18-25).

[0009] Preferably, in step S2, the mass ratio of sodium polyacrylate, sodium hexametaphosphate and triethanolamine is (20-40): (15-35): (2-8), and the mass ratio of the composite grinding aid to the fibrous light calcium carbonate is (0.002-0.02): 1.

[0010] Preferably, in step S3, after pre-grinding, the diameter of the flaky calcium carbonate is 0.4-1 μm.

[0011] Preferably, in step S4, the mass of the silane coupling agent accounts for 0.5-2% of the total mass of the pre-ground slurry, the silane coupling agent and the nano-sheet-shaped all-silicon molecular sieve.

[0012] Due to the special chemical structure of the silane coupling agent, its organic functional group methoxy can be well combined with the polymer substrate, thereby improving the dispersibility of inorganic substances in the polymer and improving the performance of the material.

[0013] Preferably, in step S4, after secondary grinding, the diameter of the flaky calcium carbonate is 0.1-0.5 μm.

[0014] In a second aspect, the present invention provides a flaky calcium carbonate composite material, which is prepared by the above-mentioned preparation method of the flaky calcium carbonate composite material.

[0015] In a third aspect, the present invention provides an application of the above-mentioned flaky calcium carbonate composite material, wherein 50-90 parts of polypropylene resin, 10-50 parts of flaky calcium carbonate composite material, 0.2-0.5 parts of antioxidant and 0.1-0.5 parts of lubricant are mixed for 5-10 minutes to obtain a uniform mixture; the mixture is added from the main feeding port of the extruder, and the temperature of the extruder is: 160-180°C in zone one, 190-220°C in zone two, 190-220°C in zone three, 190-220°C in zone four, 190-220°C in zone five, 190-220°C in zone six, 190-220°C in zone seven, 190-220°C in zone eight, and 190-220°C in zone nine, and after melting, extrusion, cooling, pelletizing, and drying are performed to obtain modified polypropylene.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention realizes the exfoliation of calcium carbonate by a two-step method. First, in the pre-grinding stage, the fibrous light calcium carbonate with a high aspect ratio is initially exfoliated to obtain a calcium carbonate powder with a high lamellar degree; then, in the secondary grinding stage, a nano-flaky all-silicon molecular sieve is introduced. Since the structural rigidity of the molecular sieve is significantly stronger than that of the calcium carbonate lamella, it plays the role of a grinding carrier in the secondary grinding process, effectively preventing the secondary grinding from damaging the calcium carbonate lamella structure. The diameter of the flaky calcium carbonate prepared by the preparation method of the flaky calcium carbonate composite material of the present invention is 0.1-0.5 μm.

[0017] 2. The present invention uses nano-flaky all-silicon molecular sieves as grinding media to ensure that in the powder obtained after grinding, these nano-flaky all-silicon molecular sieves are evenly distributed on the surface of the calcium carbonate powder. Since the pore size and shape of the nano-flaky all-silicon molecular sieves are specific, gas molecules of specific size and shape are allowed to enter its internal pores. Due to the limitation of spatial freedom and the interaction between the adsorbed gas molecules and the surface of the nano-flaky all-silicon molecular sieves such as van der Waals forces and hydrogen bonds, the nano-flaky all-silicon molecular sieves can selectively adsorb certain harmful gases, and ultimately the modified polypropylene prepared using the flaky calcium carbonate composite material has the function of adsorbing harmful gases, and is more environmentally friendly to use. DETAILED DESCRIPTION

[0018] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0019] In the following examples and comparative examples, the sources of raw materials are as follows: Polypropylene resin: homopolymer polypropylene, PP Z30S, Zhenhai Refining and Chemical Company of Sinopec; Antioxidants: Antioxidant 1010, Antioxidant 168, Tianjin Lianlong New Materials Co., Ltd.; Lubricant: calcium stearate, Shandong Baolilai Plastic Additives Co., Ltd.; Silicon source: silica sol TM-40, sodium silicate, Sigma-Aldrich; tetraethyl orthosilicate, Merck; Alkali source: NaOH, Chinese medicine; Template: Tetrapropylammonium hydroxide, Merck; Tetrapropylammonium bromide, Tetraethylammonium bromide, MacLean; Silane coupling agent: KH-550, Hangzhou Jessica Chemical Co., Ltd.

[0020] Example 1 The preparation method of the flaky calcium carbonate composite material of this embodiment comprises the following steps: (1) Preparation of nanosheet all-silicon molecular sieve TM-40, NaOH, tetrapropylammonium hydroxide and deionized water in a molar ratio of 1:3:0.04:20 were mixed to form a sol at room temperature. After aging for 3 days, the sol was hydrothermally synthesized at 140°C for 12 hours. The obtained crystals were repeatedly rinsed with deionized water, centrifuged, dried and calcined to remove the template agent tetrapropylammonium hydroxide, thereby obtaining a nano-sheet-shaped all-silicon molecular sieve. (2) Preparation of flaky calcium carbonate composite materials S1 adds fibrous light calcium carbonate into water, wherein the fibrous light calcium carbonate accounts for 60% of the total mass of the fibrous light calcium carbonate and water; S2 adds a composite grinding aid of sodium polyacrylate, sodium hexametaphosphate and triethanolamine in a mass ratio of 20:15:2, and the mass ratio of the composite grinding aid to the fibrous light calcium carbonate is 0.002:1, and a uniform slurry is obtained after dispersion; S3 pre-grinds the slurry by a planetary grinder at 70 r / min for 50 min to pre-strip the fibrous light calcium carbonate to form lamellar calcium carbonate with a diameter of 0.9 μm; S4: adding silane coupling agent KH-550 and the nano-flaky all-silicon molecular sieve prepared in step (1) to the pre-ground slurry, and performing secondary grinding at 60 r / min for 120 min to obtain a uniform mixed slurry, wherein the diameter of the flaky calcium carbonate is 0.1 μm; wherein the mass of the nano-flaky all-silicon molecular sieve accounts for 5% of the total mass of the pre-ground slurry, the coupling agent and the nano-flaky all-silicon molecular sieve, and the mass of the silane coupling agent KH-550 accounts for 0.5% of the total mass of the pre-ground slurry, the silane coupling agent and the nano-flaky all-silicon molecular sieve; The S5 mixed slurry was repeatedly washed with deionized water and centrifuged to obtain a flaky calcium carbonate composite material.

[0021] The flaky calcium carbonate composite material prepared in this example is used to prepare modified polypropylene, and the specific preparation method is as follows: 10 parts of flaky calcium carbonate composite material, 90 parts of polypropylene resin, 0.1 parts of antioxidant 1010, 0.2 parts of antioxidant 168 and 0.5 parts of calcium stearate are mixed in a high mixing pot for 10 minutes to obtain a uniform mixture; the mixture is added from the main feeding port of an extruder, and the temperature of the extruder is: 170°C for zone 1, 210°C for zone 2, 210°C for zone 3, 210°C for zone 4, 210°C for zone 5, 210°C for zone 6, 210°C for zone 7, 210°C for zone 8 and 210°C for zone 9; after melting, extrusion, cooling, pelletizing and drying are performed, to obtain modified polypropylene.

[0022] Example 2 The preparation method of the flaky calcium carbonate composite material of this embodiment comprises the following steps: (1) Preparation of nanosheet all-silicon molecular sieve Tetraethyl orthosilicate, NaOH, tetrapropylammonium bromide and deionized water in a molar ratio of 1:2:0.02:18 were mixed to form a sol at room temperature. After aging for 4 days, the sol was hydrothermally synthesized at 130°C for 16 hours. The obtained crystals were repeatedly rinsed with deionized water, centrifuged, dried and calcined to remove the template agent tetrapropylammonium hydroxide, thereby obtaining a nano-sheet-shaped all-silicon molecular sieve. (2) Preparation of flaky calcium carbonate composite materials S1 adds fibrous light calcium carbonate into water, wherein the fibrous light calcium carbonate accounts for 70% of the total mass of the fibrous light calcium carbonate and water; S2 adds a composite grinding aid of sodium polyacrylate, sodium hexametaphosphate and triethanolamine in a mass ratio of 30:25:5, and the mass ratio of the composite grinding aid to the fibrous light calcium carbonate is 0.01:1, and a uniform slurry is obtained after dispersion; S3 pre-grinds the slurry by a planetary grinder at 100 r / min for 40 min to pre-strip the fibrous light calcium carbonate to form lamellar calcium carbonate with a diameter of 1 μm; S4: adding silane coupling agent KH-550 and the nano-flaky all-silicon molecular sieve prepared in step (1) to the pre-ground slurry, and performing secondary grinding at 70 r / min for 100 min to obtain a uniform mixed slurry, wherein the diameter of the flaky calcium carbonate is 0.3 μm; wherein the mass of the nano-flaky all-silicon molecular sieve accounts for 50% of the total mass of the pre-ground slurry, the coupling agent and the nano-flaky all-silicon molecular sieve, and the mass of the silane coupling agent KH-550 accounts for 1% of the total mass of the pre-ground slurry, the silane coupling agent and the nano-flaky all-silicon molecular sieve; The S5 mixed slurry was repeatedly washed with deionized water and centrifuged to obtain a flaky calcium carbonate composite material.

[0023] The flaky calcium carbonate composite material prepared in this example is used to prepare modified polypropylene, and the specific preparation method is as follows: 20 parts of flaky calcium carbonate composite material, 80 parts of polypropylene resin, 0.1 parts of antioxidant 1010, 0.1 parts of antioxidant 168 and 0.1 parts of calcium stearate are mixed in a high mixing pot for 5 minutes to obtain a uniform mixture; the mixture is added from the main feeding port of an extruder, and the temperatures of the extruder are: 160°C for zone 1, 190°C for zone 2, 190°C for zone 3, 190°C for zone 4, 190°C for zone 5, 190°C for zone 6, 190°C for zone 7, 190°C for zone 8 and 190°C for zone 9; after melting, extrusion, cooling, pelletizing and drying are performed, to obtain modified polypropylene.

[0024] Example 3 The preparation method of the flaky calcium carbonate composite material of this embodiment comprises the following steps: (1) Preparation of nanosheet all-silicon molecular sieve Sodium silicate, NaOH, tetraethylammonium bromide and deionized water in a molar ratio of 1:4:0.06:25 were mixed to form a sol at room temperature. After aging for 1 day, the sol was hydrothermally synthesized at 160°C for 10 hours. The obtained crystals were repeatedly rinsed with deionized water, centrifuged, dried and calcined to remove the template agent tetrapropylammonium hydroxide, thereby obtaining a nano-sheet-shaped all-silicon molecular sieve. (2) Preparation of flaky calcium carbonate composite materials S1 adds fibrous light calcium carbonate into water, wherein the fibrous light calcium carbonate accounts for 80% of the total mass of the fibrous light calcium carbonate and water; S2 adds a composite grinding aid of sodium polyacrylate, sodium hexametaphosphate and triethanolamine in a mass ratio of 40:35:8, and the mass ratio of the composite grinding aid to the fibrous light calcium carbonate is 0.02:1, and a uniform slurry is obtained after dispersion; S3 pre-grinds the slurry by a planetary grinder at 150 r / min for 30 min to pre-strip the fibrous light calcium carbonate to form lamellar calcium carbonate with a diameter of 0.4 μm; S4: adding silane coupling agent KH-550 and the nano-flaky all-silicon molecular sieve prepared in step (1) to the pre-ground slurry, and performing secondary grinding at 80 r / min for 60 min to obtain a uniform mixed slurry, wherein the diameter of the flaky calcium carbonate is 0.5 μm; wherein the mass of the nano-flaky all-silicon molecular sieve accounts for 70% of the total mass of the pre-ground slurry, the coupling agent and the nano-flaky all-silicon molecular sieve, and the mass of the silane coupling agent KH-550 accounts for 2% of the total mass of the pre-ground slurry, the silane coupling agent and the nano-flaky all-silicon molecular sieve; The S5 mixed slurry was repeatedly washed with deionized water and centrifuged to obtain a flaky calcium carbonate composite material.

[0025] The flaky calcium carbonate composite material prepared in this example is used to prepare modified polypropylene, and the specific preparation method is as follows: 50 parts of flaky calcium carbonate composite material, 50 parts of polypropylene resin, 0.3 parts of antioxidant 1010, 0.2 parts of antioxidant 168 and 0.3 parts of calcium stearate are mixed in a high mixing pot for 8 minutes to obtain a uniform mixture; the mixture is added from the main feeding port of an extruder, and the temperature of the extruder is: 180°C for zone one, 220°C for zone two, 220°C for zone three, 220°C for zone four, 220°C for zone five, 220°C for zone six, 220°C for zone seven, 220°C for zone eight and 220°C for zone nine; after melting, the mixture is extruded, cooled, pelletized and dried to obtain modified polypropylene.

[0026] Comparative Example 1 The difference from Example 1 is that, when preparing the modified polypropylene, commercially available light calcium carbonate is used to replace the flaky calcium carbonate composite material in Example 1.

[0027] Comparative Example 2 The difference from Example 2 is that, when preparing the modified polypropylene, commercially available light calcium carbonate is used to replace the flaky calcium carbonate composite material in Example 2.

[0028] Comparative Example 3 The difference from Example 1 is that when preparing the flaky calcium carbonate composite material, step S4 is not performed, and finally flaky calcium carbonate is obtained and used to prepare modified polypropylene.

[0029] Comparative Example 4 The difference from Example 1 is that in step S3, during pre-grinding, the rotation speed is 250 r / min and the grinding time is 90 min.

[0030] Comparative Example 5 The difference from Example 1 is that in step S4, during the secondary grinding, the rotation speed is 120 r / min and the grinding time is 180 min.

[0031] The modified polypropylene prepared in Examples 1-3 and Comparative Examples 1-5 was subjected to performance tests, and the test results are shown in Table 1. The performance test standards and methods are as follows: the density was tested according to "GB / T 1033 Determination of density of non-foamed plastics", the tensile strength was tested according to "GB / T 1040 Determination of tensile properties of plastics", the flexural modulus was tested according to "GB / T 9341 Determination of flexural properties of plastics", the cantilever beam notched impact was tested according to "GB / T1843 Determination of cantilever beam impact strength of plastics", the heat deformation temperature was tested according to "GB / T 1634 Determination of load deformation temperature of plastics", and the odor test was tested according to "PV3900 Public Odor Test Standard".

[0032] Table 1 Performance test results of modified polypropylene prepared in Examples 1-3 and Comparative Examples 1-5

[0033] As can be seen from Table 1, the flaky calcium carbonate composite material prepared by the present invention is applied to the preparation of modified polypropylene, and the prepared modified polypropylene has excellent mechanical properties and good adsorption. By comparing Examples 1-2 and Comparative Examples 1-2, it can be seen that the rigidity and heat deformation temperature of the modified polypropylene prepared by using the flaky calcium carbonate composite material prepared by the present invention are significantly improved, and the odor level is reduced by about 0.3CLASS. As can be seen from Example 1 and Comparative Example 3, since the flaky calcium carbonate used in Comparative Example 3 does not contain nano-flaky all-silicon molecular sieves and is subjected to secondary grinding, the rigidity and heat resistance of the prepared modified polypropylene are slightly reduced; at the same time, due to the lack of gas adsorption of nano-flaky all-silicon molecular sieves, the odor level of the prepared modified polypropylene is increased and the gas adsorption is reduced. In addition, it can be seen from Comparative Examples 4-5 that during pre-grinding and secondary grinding, if the grinding is excessive, the structure of the flaky calcium carbonate composite material will be destroyed, resulting in a decrease in the rigidity and heat resistance of the modified polypropylene.

Claims

1. A method for preparing a flaky calcium carbonate composite material, characterized in that: The following steps are involved: (1) Preparation of nanosheet all-silicon molecular sieve A silicon source, an alkali source, a template agent and deionized water are mixed to form a sol at room temperature, and after aging for 1-4 days, a hydrothermal synthesis is performed at 130-160°C for 10-16 hours. The obtained crystals are repeatedly rinsed with deionized water, centrifuged, dried and calcined to remove the template agent, thereby obtaining a nano-sheet-shaped all-silicon molecular sieve; (2) Preparation of flaky calcium carbonate composite materials S1: adding fibrous light calcium carbonate into water, wherein the fibrous light calcium carbonate accounts for 60-80% of the total mass of the fibrous light calcium carbonate and water; S2 adds a composite grinding aid and disperses to obtain a uniform slurry; the composite grinding aid is sodium polyacrylate, sodium hexametaphosphate and triethanolamine; S3 pre-grinds the slurry at a rotation speed of 70-150 r / min and a grinding time of 30-50 min to pre-strip the fibrous light calcium carbonate to form lamellar calcium carbonate; S4: adding a silane coupling agent and the nano-sheet-shaped all-silicon molecular sieve prepared in step (1) to the pre-ground slurry, and performing secondary grinding at a rotation speed of 60-80 r / min and a grinding time of 60-120 min to obtain a uniform mixed slurry; wherein the mass of the nano-sheet-shaped all-silicon molecular sieve accounts for 5-70% of the total mass of the pre-ground slurry, the silane coupling agent and the nano-sheet-shaped all-silicon molecular sieve; The S5 mixed slurry was repeatedly washed with deionized water and centrifuged to obtain a flaky calcium carbonate composite material.

2. The method for preparing a flaky calcium carbonate composite material according to claim 1, wherein In step (1), the silicon source is silica sol, tetraethyl orthosilicate or sodium silicate; the alkali source is NaOH; and the template agent is tetrapropylammonium hydroxide, tetrapropylammonium bromide or tetraethylammonium bromide.

3. The preparation method of the flaky calcium carbonate composite material as claimed in claim 1, characterized in that, In step (1), the molar ratio of the silicon source, the alkali source, the template and the deionized water is 1:(2-4):(0.02-0.06):(18-25).

4. The method for preparing a flaky calcium carbonate composite material according to claim 1, wherein In step S2, the mass ratio of sodium polyacrylate, sodium hexametaphosphate and triethanolamine is (20-40): (15-35): (2-8), and the mass ratio of the composite grinding aid to the fibrous light calcium carbonate is (0.002-0.02):

1.

5. The method for preparing a flaky calcium carbonate composite material according to claim 1, wherein In step S3, after pre-grinding, the diameter of the flaky calcium carbonate is 0.4-1 μm.

6. The method for preparing a flaky calcium carbonate composite material according to claim 1, wherein In step S4, the mass of the silane coupling agent accounts for 0.5-2% of the total mass of the pre-ground slurry, the silane coupling agent and the nano-sheet-shaped all-silicon molecular sieve.

7. The method for preparing a flaky calcium carbonate composite material according to claim 1, wherein In step S4, after secondary grinding, the diameter of the flaky calcium carbonate is 0.1-0.5 μm.

8. A flaky calcium carbonate composite material, characterized in that: The flaky calcium carbonate composite material is prepared by the preparation method according to any one of claims 1 to 7.

9. The use of the flaky calcium carbonate composite material as claimed in claim 8, characterized in that: 50-90 parts of polypropylene resin, 10-50 parts of flaky calcium carbonate composite material, 0.2-0.5 parts of antioxidant and 0.1-0.5 parts of lubricant are mixed for 5-10 minutes to obtain a uniform mixture; the mixture is added from the main feeding port of an extruder, and the temperature of the extruder is: 160-180°C in the first zone, 190-220°C in the second zone, 190-220°C in the third zone, 190-220°C in the fourth zone, 190-220°C in the fifth zone, 190-220°C in the sixth zone, 190-220°C in the seventh zone, 190-220°C in the eighth zone and 190-220°C in the ninth zone; after melting, the mixture is extruded, cooled, pelletized and dried to obtain modified polypropylene.

Citation Information

Patent Citations

  • Method for preparing flaky ground calcium carbonate powder

    CN101514028A

  • Production method for calcium carbonate residue carbonized nutrient soil

    CN104945173A

  • Preparing method of inflame-retarding type big-diameter plate-shaped calcium carbonate

    CN107055585A

  • Preparation method of large-diameter flake-shaped calcium carbonate

    CN107244686A

  • Calcium carbonate / zeolite-based compound composite and article using the same

    JP2012106926A